(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
Brazil stands out in the international scenario as the largest producer of sugarcane, processing billions of tons. Thus, this activity generates residues, such as ashes from bagasse burning and straw from sugarcane cleaning and from the production of sugar, alcohol and thermal energy. Therefore, the objective was to evaluate the initial performance and chlorophyll content of pigeon pea and the chemical attributes of the soil after application of ash doses. The experiment was conducted in 2021, in a greenhouse located in southwestern Goiás, Brazil. The design used was completely randomized, composed of five ash doses: 10, 20, 30, 40 and 50 Mg ha-1 and a control treatment, with four replicates, totaling 24 experimental units. The use of only ash as a fertilizer source causes linear increases in the initial growth of pigeon pea and in the contents of total chlorophyll and chlorophyll b, reaching the maximum increments with the estimated ash doses of 35.9 and 38.9 Mg ha-1. Applications of high ash doses promoted improvements in soil fertility, with increase in pH, P, K and base saturation as well as reduction in aluminum content and aluminum saturation. Calcium and magnesium contents reached the maximum increments with the estimated ash doses of 39.5 and 66.7 Mg ha-1, respectively.